A quality by design (QbD) case study on enteric-coated pellets: Screening of critical variables and establishment of design space at laboratory scale - Shuling Kan; Jing Lu; Jianping Liu; Junlin Wang; Yi Zhao (Elsevier, 2014)
The study aims to prepare naproxen enteric-coated pellets (NAP-ECPs) by fluid-bed coating using QbD principle. Risk assessment was firstly performed by using failure mode and effect analysis (FMEA) methodology. A Plackett-Burman design was then used for assessment of the most important variables affecting enteric-coated pellets characteristics. A Box-Behnken design was subsequently used for investigating the main, interactive, and quadratic effects of these variables on the response. By FMEA we discovered that eight factors should be considered to be high/important risk variables as compared with others. The responses of acid resistance and cumulative drug release were taken as critical quality attributes (CQAs). Pareto ranking analyses indicated that the coating weight gain (X7), triethyl citrate percentage (X1) and glycerol monostearate percentage (X2) were the most significant factors affecting the selected responses out of the eight high-risk variables. Optimization with response surface method (RSM) further fully clarified the relationship between X7, X1, X2 and CQAs, and design space was established based on the constraints set on the responses. Due to the extreme coincidence of the predicted value generated by model with the observed value, the accuracy and robustness of the model were confirmed. It could be concluded that a promising NAP-ECPs was successfully designed using QbD approach in a laboratory scale.